An Initial Examination of Student Preferences between Visual and Non-visual Modes of Case Processing - Ishiyama, F. Ishu (Canadian Journal of Counselling and Psychotherapy, 2011)
The present study examined counselling students' preferences between two modes of conceptualizing and presenting interview cases. Subjective ratings on visual and non-visual methods were obtained from 19 students who were exposed to both modes in an elementary counselling course. The visual mode using metaphors and drawings was rated more positively than the non-visual mode on two areas of case processing (i.e., conceptualization and presentation). The differences were statistically significant. Students considered the visual mode more effective in developing an understanding of the client and the helping process. It was also considered more effective in facilitating presenters' self-expression and exploration of feelings, in focusing the discussion, in summarizing the case, and in maintaining objectivity in case presentation. An example of visual case processing is provided, and the study's limitations and practical implications are discussed.